Development of a global-local geometric planning approach to automated part finishing processes. (1st October 2007) - Sun, Y.W.; Meng, L.H.; Guo, D.M.; Jia, Z.Y.
A conformal map-based global and local geometric planning approach to the automated part finishing processes is presented in this paper. With the consideration of the complexity and difficulty of direct planning paths in 3D physical space, the proposed method first generates the paths in the given planar region and then inversely maps the paths on the machined surface. Some detailed issues such as step length determination and path interval computation are also discussed. By means of the mapping mode, some complicated path patterns such as spiral paths and multi-directional paths can easily be designed and obtained. The illustrated example of geometric planning shows the validity of the proposed method.